2016
DOI: 10.5468/ogs.2016.59.4.279
|View full text |Cite
|
Sign up to set email alerts
|

Association of plasma adiponectin and leptin levels with the development and progression of ovarian cancer

Abstract: ObjectiveDecreased adiponectin and increased leptin plasma concentrations are believed to be associated with the occurrence and progression of cancers such as endometrial cancer and breast cancer. The aim of this study was to explore the association of plasma adiponectin and leptin levels with the development and progression of ovarian cancer.MethodsFor patients with ovarian cancer and the control group, adiponectin and leptin levels were measured; anthropometric data were obtained during a chart review. Stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 31 publications
1
34
2
Order By: Relevance
“…Moreover, it has been reported that elevated insulin levels also lead to a leptin overexpression: increased leptin plasma concentrations are believed to be associated with the occurrence and progression of endometrial and ovarian cancer [13][14][15]. Furthermore, leptin can also upregulate vascular endothelial growth factor (VEGF), a hallmark of malignant tumor development [16].…”
Section: Biological Links Between T2d and Gynecological Cancersmentioning
confidence: 99%
“…Moreover, it has been reported that elevated insulin levels also lead to a leptin overexpression: increased leptin plasma concentrations are believed to be associated with the occurrence and progression of endometrial and ovarian cancer [13][14][15]. Furthermore, leptin can also upregulate vascular endothelial growth factor (VEGF), a hallmark of malignant tumor development [16].…”
Section: Biological Links Between T2d and Gynecological Cancersmentioning
confidence: 99%
“…Women with OC often have no typical symptoms until the disease reaches an advanced stage with peritoneal dissemination and massive ascites [2]. Debulking surgery and chemotherapy are currently the most commonly used therapies for OC treatment [3], but the 5-year survival rate of OC patients is only 45% [4]. It is necessary to explore new molecular mechanisms and to identify new potential therapeutic targets to improve OC treatment.…”
mentioning
confidence: 99%
“…There is some evidence that lower levels of leptin [ 44 ] and higher levels of prolactin [ 45 ] might be associated with increased risk of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%